Wireless Network based- Cisco Systems Study - Israa Falih Muslm (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Building reliable networks that are able to function even when some parts of them are damaged or broken Expensive in Africa, but despite that these were all of our main drivers .The vehicles are in our head office equipped for VPN and Virtual Private Network equipment Even if some of its parts fail, which we have been testing periodically to avoid any surprises unbearable. As for the central stations, we have taken a decision not to install a backup router Rather, we kept these backup routers within the site as spare parts without 3 hours at worst (if - installed. We found that the service was interrupted for a period ranging between the call is cut off at one o'clock in the morning on the weekend, for example) is considered acceptable from a destination view customers. The equipment can be used by the technical support personnel on duty on holidays Back-up equipment (such as transmitting and receiving equipment and electrical supply units) within Dedicated emergency locker.The logical and physical network design was characterized by maximum flexibility, as was the structure of the network tunnels Certified in Nairobi for superior flexibility to meet customers' requirements that VPN private virtual For example, setting up customer connections in order to increase their capacity within the minimum hours of network activity Backup storage to another location. We were also able to sell multiple connections to separate each destination Therefore, we increase the return on our investments by providing more services to customers (such as monitoring by monitoring CCTV remote and video surveillance devices